Insulin requirement profiles of short-term intensive insulin therapy in patients with newly diagnosed type 2 diabetes and its association with long-term glycemic remission. Issue 2 (May 2015) - Liu, Liehua; Ke, Weijian; Wan, Xuesi; Zhang, Pengyuan; Cao, Xiaopei; Deng, Wanping; Li, Yanbing
Highlights There is a decline of daily insulin dose after euglycemia achieved. The decrement of daily insulin dose is related to reduction of insulin resistance during the therapy. Patients with lowest decline of insulin dose had higher risk of hyperglycemic relapse.